Development of an in vitro model to investigate repeat ocular exposure - Wilkinson, Peter J. (2006)
The Draize eye irritation test has been widely adopted as the "gold standard" to evaluate the potential eye irritation of a wide range of chemicals and formulations, including; pharmaceuticals, cosmetics, and their raw ingredients. The rationale for pursuing the development of human ocular based in vitro alternatives is to provide greater confidence in the prediction of human reactions to mild and moderate chemicals. This is particularly important with the implementation of the EC White Paper, "Strategy for a future chemicals policy" (2001) that is estimated to require the testing of approximately 30,000 'existing' chemicals by 2012.